2022
DOI: 10.1590/0037-8682-0479-2021
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Chagas disease in urban and rural indigenous populations of the south of Gran Chaco

Abstract: Background: In Latin America, Chagas disease is endemic, with a high prevalence in rural indigenous communities and an increasing prevalence in urban areas owing to migration from rural areas with active vector transmission. This study aimed to assess differences in the prevalence of Chagas disease in urban and rural moqoit communities, one of the main ethnic indigenous groups in the south of Gran Chaco.Methods: A seroprevalence study was conducted in six moqoit populations in the Santa Fe province, Argentina.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Although, in the present work, it was found that the risk of infestation is present, the residual effect of insecticides would keep homes free of infestation for the time being; hence, the prevalence found is due to the fact that the infection is chronic, and serology remains positive for life. In this sense, other authors [ 7 ] found greater seroprevalence in urban populations than in rural ones, due to the migration to the cities of families that had worse social and sanitary conditions in rural areas.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Although, in the present work, it was found that the risk of infestation is present, the residual effect of insecticides would keep homes free of infestation for the time being; hence, the prevalence found is due to the fact that the infection is chronic, and serology remains positive for life. In this sense, other authors [ 7 ] found greater seroprevalence in urban populations than in rural ones, due to the migration to the cities of families that had worse social and sanitary conditions in rural areas.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, this activity was developed with these three communities due to the feasibility of access, and it should not be ruled out that, in the most remote communities and with greater difficulties to access, the risks and seroprevalence are different. In this sense, a seroprevalence study in the region [ 7 ] found that Chagas disease was more frequent in urban communities than in rural ones, because people with the worst socioenvironmental conditions migrated more frequently to urban settings and, therefore, these people were the most at risk of infection. This point may also explain the higher seroprevalence found in the present work compared to [ 7 ], in which urban and rural communities were studied.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Control measures should instead focus on other reinfestation sources like sylvatic foci or domestic foci that survive insecticide spraying. A possible, unlikely exception would be the case when travel or migration is from areas where Chagas disease is endemic to areas where it is not, for example, from rural communities to urban ones [49]. Such a scenario could be considered in future work but would require significant modeling changes as the model here specifically considers travel between rural villages, which have quite different transmission dynamics than urban settings.…”
Section: Discussionmentioning
confidence: 99%